Effects of surface-modified biochars and activated carbon on the transformation of soil inorganic nitrogen and growth of maize under chromium stress. (July 2019) - Zhu, Yuen; Li, Hua; Wu, Yi; Yin, Xin-An; Zhang, Guixiang
Abstract: Elevated chromium (Cr) level is challenging agricultural production and affecting soil biochemical process. This study evaluated the effect of amendments including surface-modified biochars (HBC: acid washing, Fe(III)-HBC: ferric iron loading, nZVI-HBC: nanoscale zero-valent iron loading) and activated carbon on hexavalent chromium (Cr(VI)) removal in soil and on N cycling enzyme activities, transformation of soil inorganic nitrogen, and growth of maize under Cr stress. The results showed that amendments increased Cr(VI) removal by 72.9%–96.34% at three levels of spiked Cr(VI) (low: 125 mg kg −1, moderate: 250 mg kg −1, high: 500 mg kg −1 ). Under low Cr stress, amendments generally significantly decreased urease and nitrite reductase activities but increased nitrate reductase activity ( p < 0.05). The NH4 + -N content had a significant positive correlation with urease activity ( p < 0.01), while both NO2 − -N and NO3 − -N were absent correlations with N cycling enzyme studied. Amendments decreased NH4 + -N/NO3 − -N ratio under low Cr stress but increased it under moderate Cr stress, although the difference was not significant. Under high Cr stress, only Fe(III)-HBC significantly increased NH4 + -N/NO3 − -N ratio (p < 0.05). The decrease and increase of NH4 + -N/NO3 − -N ratios indicate the enhancement of nitrification and denitrification, respectively. The increase in Cr(VI) removal by amendments contributed to the increase in the migration of NO3 − -N from roots to shoots. Amendments (except for nZVI-HBC in soil under low Cr stress) increased maize height by 20%–59%. Under low Cr stress, however, nZVI-HBC significantly decreased maize height by 65% ( p < 0.05), indicating the toxic effect of nZVI on maize growth overwhelmed low Cr stress. Graphical abstract: Image 1 Highlights: Amendments (modified biochars and activated carbon) increased Cr(VI) removal in soil Effect of amendment on N cycling enzyme activity depended on enzyme type and Cr stress Effect of amendment on transformation of SIN was significantly related to Cr stress Removal of Cr(VI) by amendment increased migration of NO3 − -N from maize root to shoot Amendment generally played positive role in maize growth under Cr stress